Stimulating housing policy and housing tenure choice: Evidence from the G7 Countries - Eugeniya Malinskaya; Konstantin A. Kholodilin (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
Housing affordability is a hotly debated issue on global scale. A lack of affordable housing of decent quality is a chronic problem in urban areas. Governments try to alleviate it by stimulating homeownership among middle-income households and providing social housing for the low-income households. Such policies are very costly. Thus, this study aims to assess at least tentatively the effectiveness of the policies supporting construction of affordable housing. We do this using a novel index of the governmental support of affordable housing construction. It covers G7 countries between 1919 and 2020. We conclude from our empirical analysis that governmental policy indeed positively affects homeownership rates and social housing rates. Thus, the government can contribute to the provision of the affordable housing, although the cost of this policy cannot be quantified yet.
Keywords: K25; R38; C23; C43; 330; housing policy; affordable housing; homeownership rate; social housing; G7 countries; regulation indices